2022
DOI: 10.1002/ar.24875
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the preterm human heart: What do we know so far?

Abstract: Globally, preterm birth affects more than one in every 10 live births. Although the short-term cardiopulmonary complications of prematurity are well known, long-term health effects are only now becoming apparent. Indeed, preterm birth has been associated with elevated cardiovascular morbidity and mortality in adulthood. Experimental animal models and observational human studies point toward changes in heart morphology and function from birth to adulthood in people born preterm that may contribute to known long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…Although the birth rate is low among advanced countries, premature infants (defined as delivery at <32 weeks of gestational age) are more likely to suffer from respiratory distress syndrome, sepsis, intraventricular hemorrhage, and necrotizing enterocolitis shortly after birth [ 1 , 2 ]. Furthermore, several studies have reported that an increase in the frequency of chronic diseases such as diabetes, obesity, cardiovascular diseases, and hypertensive disorders in adulthood can be attributed to an influence of the intrauterine environment and preterm birth [ 3 , 4 , 5 , 6 , 7 ]. Additionally, preterm birth is associated with elevated cardiovascular morbidity and mortality in adulthood [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the birth rate is low among advanced countries, premature infants (defined as delivery at <32 weeks of gestational age) are more likely to suffer from respiratory distress syndrome, sepsis, intraventricular hemorrhage, and necrotizing enterocolitis shortly after birth [ 1 , 2 ]. Furthermore, several studies have reported that an increase in the frequency of chronic diseases such as diabetes, obesity, cardiovascular diseases, and hypertensive disorders in adulthood can be attributed to an influence of the intrauterine environment and preterm birth [ 3 , 4 , 5 , 6 , 7 ]. Additionally, preterm birth is associated with elevated cardiovascular morbidity and mortality in adulthood [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have reported that an increase in the frequency of chronic diseases such as diabetes, obesity, cardiovascular diseases, and hypertensive disorders in adulthood can be attributed to an influence of the intrauterine environment and preterm birth [ 3 , 4 , 5 , 6 , 7 ]. Additionally, preterm birth is associated with elevated cardiovascular morbidity and mortality in adulthood [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from a prenatal to postnatal environment at birth is believed to be a critical step in CM development and transition to an adult state. One aspect that is worthy of consideration is how this process is affected in preterm birth scenarios (with a global prevalence of more than 10% of live births) and how an unprepared heart adapts to the sudden unexpected environmental change and interruption of a critical phase in CM maturation ( 102 ). This is of interest since the transcriptomic analysis of hiPSC-CMs indicate the limitation of current CM differentiation strategies in which CM s resemble the first trimester fetal heart which further may progress to around the equivalent of a second trimester fetal heart upon maturation treatment ( 103 ).…”
Section: The Impact Of Preterm Birth On Cardiomyocyte Maturationmentioning
confidence: 99%
“…Other studies using cardiovascular magnetic resonance imaging (CMR) demonstrate that preterm-born adults have anatomical differences compared with those born at term, namely smaller ventricles and altered myocardial mass, with increased myocardial fibrosis, leading to impaired function (see Ref. [47] for a review). This cardiac phenotype could interact with higher blood pressures and physiological stress to accelerate progression of cardiovascular disease, but longer-term longitudinal studies are required to confirm this trajectory.…”
Section: Cardiovascular and Metabolic Outcomesmentioning
confidence: 99%